Quantifying the impact of a real world cooperative-ITS deployment across multiple cities. (September 2018) - Edwards, S.; Hill, G.; Goodman, P.; Blythe, P.; Mitchell, P.; Huebner, Y.
Abstract: Cooperative Intelligent Transport Systems (C-ITS) - Connected Vehicle technology in the USA - where vehicle and roadside infrastructure communicates to deliver more intelligent traffic management, is one of a range of ITS technologies emerging as a key component in pursuit of the wider objectives of improved urban mobility. This paper presents the Compass4D project, which deployed a C-ITS system in seven European cities and coordinated the common evaluation of the technology for three services focusing specifically on safety and environmental objectives under real-world driving conditions. The significance of the Compass4D deployments and results provides some of the first evidence of the effectiveness of C-ITS in real world conditions. Both light and heavy vehicles showed efficiency savings of 2–6%. Equipped buses exhibited a variety of results with one pilot site showing a reduction of greater than 200gCO2 per bus route per trip whilst other buses showed an increase in total emissions. The paper presents results from both field trials and microscopic simulation studies (to understand the network- or city-wide impacts of the technology). It discusses the results in detail before outlining the potential for further deployment in terms of the impact on energy efficiency and environmental objectives. Government and road operators will benefit from the results to gain an understanding of the potential impact of services given specific deployment characteristics.